Green Intellectual Capital and Sustainability Performance: Does Environmental Leadership Matter? - Firmansyah, Amrie; Qadri, Resi Ariyasa; Permatasari, Paulina; Andriani, Arifah Fibri; Maratno, Sylvia Fettri Elvira (Universitas Syiah Kuala, 2024)
Objective This study investigates the impact of green human capital, green structural capital, and green relational capital, all components of green intellectual capital, on sustainability performance. Furthermore, this study considers environmental leadership a moderating component in this test.Design/Methodology This study employs primary data in the form of a questionnaire survey to research respondents, namely the top-level managers of a company. The final questionnaire used in the research was derived from 141 respondents. The data analysis test in this study uses a structural equation model.Results This study concludes that green human capital and green structural capital positively affect sustainability performance, while green relational capital does not affect sustainability performance. Environmental leadership does not strengthen the positive influence of green human capital on sustainability performance and the positive impact of green relational capital on sustainability performance. However, the interaction of environmental leadership and green relational capital has a negative effect on sustainability performance. Furthermore, environmental leadership strengthens the positive effect of green structural capital on sustainability performance.Research limitations/implications One disadvantage of this study is that most respondents came from the banking industry. As a result, the results remain narrowly focused on that industry and do not adequately reflect the organization's state. To provide more precise research results, future studies can assess sustainability performance utilizing respondents from various industries.Novelty/Originality This work in sustainable accounting has developed a rarely explored literature on utilizing green intellectual capital. Furthermore, by gathering data from a growing economy, our analysis adds to the body of information on references on long-term company performance. Furthermore, by evaluating the features of Indonesian firms, our research can be used to help design government policies governing the implementation of sustainability in the business sector.